Sport facility booking system (SFBS) - Pei Chyi, Tan (2012)
The objective of this project is to discuss Sport Facility Booking System (SFBS) in web-based application. It is based on first come first serve concept.This system is develops to simplify booking process but also improve communication ways between members and admin.For instance, announcement board and report board play the important roles in communication way between admin and member by sharing the detail. SMS function also raises the efficiency of communication function.Design of this system included system interface design and database design. System interface design is focus on interaction between system and user whereas database design is emphasizes toward data store and data retrieve.Flow chart, use case and sequence diagram are use for represent flowing process will occur when user interact with system.Rational Unified Process is a comprehensive and flexible software project development framework that embodies an iterative approach and other best practices. However,the expected result shall be planning to reduce the risk taken during the development process.